Maize Response to Low Temperatures at the Gene Expression Level: A Critical Survey of Transcriptomic Studies - Sowiński, Paweł; Fronk, Jan; Jończyk, Maciej; Grzybowski, Marcin; Kowalec, Piotr; Sobkowiak, Alicja (Frontiers in Plant Science, 2020)
Maize is a cold-sensitive plant whose physiological reactions to sub-optimal temperatures are well understood, but their molecular foundations are only beginning to be deciphered. In an attempt to identify key genes involved in these reactions we surveyed several independent transcriptomic studies addressing the response of juvenile maize to moderate or severe cold. Relatively few genes found to change expression upon cold treatment were reported in more than one study, indicating an astonishing variability of the expression changes, likely depending on the experimental design and plant material used. Nearly all these “common” genes were specific to either moderate or to severe cold and formed distinct interaction networks, indicating fundamentally different responses. Moreover, down-regulation of gene expression dominated strongly in moderate cold and up-regulation prevailed in severe cold. Very few of these genes have ever been mentioned in the literature as cold-stress-related, indicating that most response pathways remain poorly known at the molecular level. We posit that the genes identified by the present analysis are attractive candidates for further functional studies and their arrangement in complex interaction networks indicates that a re-interpretation of the present state of knowledge on the maize cold-response is justified.